MINE WATER MANAGEMENT IN THE COAL MINING PROCESS - Pranata, Andrian; Sari, Novi Kartika; Tahir, Tarmizi; Fahmi, Achmad Gus; Habibie, Hanifullah; Choiron, Dodik; Triwibowo, Didik (Universitas Sahid, 2024)
The open mining method has the potential for the formation of mine water. Mine water is characterized by a high degree of acidity which affects the life of organisms and the quality of the environment indirectly or directly, therefore it needs to be managed. This study examines mine water management at PT Adaro Indonesia. The methods used in the research were field studies and laboratory experiments. Grab sampling is used to take water samples, with the test parameters being pH, Fe and Mn metals and total suspended solid (TSS). Data analysis was carried out quantitatively and descriptively. The mine water management used is in the form of a settling pond. The settling pond consists of several compartments, namely sedimentation pond, safety pond, treatment pond and mud pond. The quality of mine water management through a series of settling ponds obtained changes in pH to 6.07, Fe metal 0.0465 mg/l, Mn metal 1.3513, and TSS 35 mg/l with an efficiency of more than 50%. The quality of mine water produced after going through management has met the established regulations, namely Decree of the Minister of Environment and Forestry No. 1347/MENLHK/SETJEN/PLA.4/12/2022.